Bortezomib plus dexamethasone vs thalidomide plus dexamethasone for relapsed or refractory multiple myeloma. Issue 5 (17th April 2018) - Iida, Shinsuke; Wakabayashi, Masashi; Tsukasaki, Kunihiro; Miyamoto, Kenichi; Maruyama, Dai; Yamamoto, Kazuhito; Takatsuka, Yoshifusa; Kusumoto, Shigeru; Kuroda, Junya; Ando, Kiyoshi; Kikukawa, Yoshitaka; Masaki, Yasufumi; et al.
Abstract : A randomized phase II selection design study (JCOG0904) was carried out to evaluate the more promising regimen between bortezomib (Bor) plus dexamethasone (Dex; BD) and thalidomide (Thal) plus Dex (TD) in Bor and Thal‐naïve patients with relapsed or refractory multiple myeloma (RRMM). Patients ≥20 and <80 years old with a documented diagnosis of symptomatic multiple myeloma (MM) who received one or more prior therapies were randomized to receive BD (Bor 1.3 mg/m 2 ) or TD (Thal 200 mg/d). In both arms, 8 cycles of induction (3‐week cycle) were followed by maintenance phase (5‐week cycle) until disease progression, unacceptable toxicity, or patient refusal. The primary end‐point was 1‐year progression‐free survival (PFS). Forty‐four patients were randomized and assigned to receive BD and TD (n = 22, each group). At a median follow‐up of 34.3 months, the 1‐year PFS in the BD and TD arms were 45.5% (95% confidence interval (CI), 24.4%‐64.3%) and 31.8% (95% CI, 14.2%‐51.1%), respectively, and the overall response rates were 77.3% and 40.9%, respectively. The 3‐year overall survival (OS) was 70.0% (95% CI, 44.9%‐85.4%) in the BD, and 48.8% (95% CI, 25.1%‐69.0%) in the TD arm. Among grade 3/4 adverse events, thrombocytopenia (54.5% vs 0.0%) and sensory peripheral neuropathy (22.7% vs 9.1%) were more frequent in BD when compared with the TD arm. Patients treated with BD had better outcomes than those treated with TD with regard to 1‐year PFS and 3‐year OS. Thus, BD was prioritized over TD for further investigations in Bor and Thal‐naïve RRMM patients. (Clinical trial registration no. UMIN000003135.) Abstract : Bortezomib plus dexamethasone showed better 1‐year progression‐free survival than thalidomide plus dexamethasone in patients with relapsed or refractory multiple myeloma.